Trace elements in ALS patients and their relationships with clinical severity. (April 2018) - Oggiano, Riccardo; Solinas, Giuliana; Forte, Giovanni; Bocca, Beatrice; Farace, Cristiano; Pisano, Andrea; Sotgiu, Maria Alessandra; Clemente, Simonetta; Malaguarnera, Michele; Fois, Alessandro Giuseppe; Pirina, Pietro; Montella, Andrea; et al.
Abstract: An exploratory study of trace elements in ALS and their relationships with clinical severity was detected. Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder that causes irreversible damage in humans, with the consequent loss of function of motoneurons (MNs), with a prognosis up to 5 years after diagnosis. Except to genetic rare cases it is not known the etiology of the disorder. Aim of our research is to investigate the possible role of heavy metals in the severity of the disease. In this study, by the use of plasma mass (ICP-MS), we have analyzed the content of essential and heavy metals such: Pb, Cd, Al, Hg, Mn, Fe, Cu, Zn, Se, Mg, and Ca, in blood, urine and hair of ALS patients and controls; moreover we divided the patients in two groups for disease severity and analyzed the difference among the groups, in order to study a possible involvement of metals in the severity of the damage. Our results suggest a protective role of Selenium, involved in protective antioxidant mechanisms, and a risk factor in the case of presence of Lead in blood. The levels of the other metals are not easy to interpret, because these may be due to life style and for essential metals a consequence of the disease condition, not a cause. Highlights: Relations of metals and progression of human ALS pathology in patients were found. Toxic and essential element were related to the ALS clinical severity. Blood Pb levels is an ALS risk factor in Sardinian patients, while Se is protective.